2020
DOI: 10.1155/2020/9190458
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity Practice and Associated Factors among Children Aged 6–23 Months in Robe Town, Bale Zone, Ethiopia

Abstract: Background. Diet diversification is essential to prepare adequate food that is useful for children’s physical and cognitive development. Despite the limited studies performed in different parts of Ethiopia, the information about the feeding practice of children in the current study area is not documented. Thus, this study intended to assess the dietary diversity practices and associated factors among children aged 6–23 months. Methods. Community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…In the present study, the overall minimum dietary diversity among lactating mothers was 23⋅6 % (95 % CI 19 %, 28 %). The present study finding is similar to the study revealed in Oromia 23 % ( 13 ) .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the overall minimum dietary diversity among lactating mothers was 23⋅6 % (95 % CI 19 %, 28 %). The present study finding is similar to the study revealed in Oromia 23 % ( 13 ) .…”
Section: Discussionsupporting
confidence: 93%
“…The design and development of the conceptual framework for the study were guided by the literature review for factors that are associated with children's DD. 3,[7][8][9]12,13,15,[17][18][19][20][21] These cover factors related to child, maternal, household, and community characteristics that impact children's diet. The main exposure variables were wealth, household food insecurity access, mother's marital status, family size, maternal age, maternal education, maternal occupation, child sex, child age in a month, paternal education, paternal occupation, and child's place of birth order.…”
Section: Independent Variablesmentioning
confidence: 99%
“…16 In Ethiopia, there is an improvement in the proportion of children who meet the MDD, 6.3% in 2005 to 13.5% in 2016; 17 however, the levels remain unacceptably low. Previous research has revealed factors connected to children's DD such as mother's age, maternal educational level, 12,18 marital status, maternal occupation, 19 ANC visit, residence, region, child's gender, birthing sequence, childbirth interval, child's age, 18 number of under-5 children, 19 currently breastfeeding, paternal educational status, household wealth status, 12,20 family size, desire for pregnancy, media exposure, antenatal and postnatal care. 17,21 Many public health measures have been carried out across Ethiopia to improve the culture of DD and the nutritional status of children.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving dietary diversity is a major challenge among resource‐poor settings in the developing world (Bedada et al 2020; Bosha et al. 2019), particularly for children in rural Ethiopian households (Girma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%